Creative students in self-paced online learning environments: an experimental exploration of the interaction of visual design and creativity - Michaela Rosar; Joshua Weidlich (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract Creativity is an increasingly recognized construct in technology-enhanced learning. However, our understanding of how creativity interacts with the design of online learning environments to affect learning experiences is still limited. For example, do creative students benefit from different learning environment designs than those benefitting their less creative peers? This experimental study (N = 187) explores this question by investigating the visual design of a self-paced online learning environment, specifically the degree of visual structure, in relation to students' creativity. Creativity was measured in different ways, along the lines of vocational/study choice, self-reported personality and behavior, and creative production. Students were randomly assigned to either a visually unstructured (experimental group) or a visually highly structured (control group) learning environment. They reported their preference, impulse for activation, and situational motivation after the learning experience. Results indicate interaction effects consistent with the role of creativity in perception and learning. More specifically, creative students reported more motivation after learning in an unstructured environment, whereas non-creative students reported relatively better learning experiences in the highly structured condition. These results contribute to resolving previous conflicting findings from separated studies, yet some ambiguities remain. Results and implications are discussed, and recommendations for future research are laid out.